DETERMINANTS OF GOING PUBLIC DECISION: THE CASE OF PT. BANK SULUTGO - Jelita, Kezia; Tulung, Joy E.; Gunawan, Emilia M. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: A lot of companies in Indonesia have already decided to go public, however, none of them are from North Sulawesi. There is a big regional company that has the desire to go public but have not go public, the company name is PT. Bank SulutGo. This research uses qualitative method and a semi-structure interview to the board of commissionaire and board of director of PT. Bank SulutGo. The interview results are supported with secondary data that are collected from the annual report of PT. Bank SulutGo, to know the requirements in Indonesia regarding going public, in which stage does PT. Bank Sulut Go is currently, and the considerations of PT. Bank SulutGo to go public. The result from this research are that PT. Bank SulutGo have already fulfill the requirements, and in the preparation stage, and the main reason they wants to go public are raising capital and increasing company’s value, while the main reason to not go public because time-consuming expense and equity dilution. PT. Bank SulutGo should improves their performance in order to go public and be the first company in North Sulawesi that is going public. Keywords: IPO, going public, going public decision, go public requirements